2019
DOI: 10.1002/anie.201912785
|View full text |Cite
|
Sign up to set email alerts
|

A Supported Nickel Catalyst Stabilized by a Surface Digging Effect for Efficient Methane Oxidation

Abstract: A surface digging effect of supported Ni NPs on an amorphous N‐doped carbon is described, during which the surface‐loaded Ni NPs would etch and sink into the underneath carbon support to prevent sintering. This process is driven by the strong coordination interaction between the surface Ni atoms and N‐rich defects. In the aim of activation of C−H bonds for methane oxidation, those sinking Ni NPs could be further transformed into thermodynamically stable and active metal‐defect sites within the as‐generated sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…[72] Furthermore, by utilizing the strong coordination interaction between the N-rich defects and surface Ni atoms, Wu and co-workers developed a surface digging effect for Ni NPs on amorphous NC, and synthesized a stable sinteringresistant supported Ni SACs on carbon nanotubes. [73] In situ TEM observations and theoretical calculations revealed that the Ni NPs on the surface would be etched and anchored in the NC support. Besides, they developed a N-doped carbon thermal atomization strategy to treat severely deactivated and sintered .…”
Section: Active Sites Of Sacsmentioning
confidence: 99%
“…[72] Furthermore, by utilizing the strong coordination interaction between the N-rich defects and surface Ni atoms, Wu and co-workers developed a surface digging effect for Ni NPs on amorphous NC, and synthesized a stable sinteringresistant supported Ni SACs on carbon nanotubes. [73] In situ TEM observations and theoretical calculations revealed that the Ni NPs on the surface would be etched and anchored in the NC support. Besides, they developed a N-doped carbon thermal atomization strategy to treat severely deactivated and sintered .…”
Section: Active Sites Of Sacsmentioning
confidence: 99%
“…Methane (CH 4 ) is an important fossil fuel and a starting point of C1 chemistry. Efficient utilization of CH 4 is an imperative task [1–7] . CH 4 is the most thermodynamically stable alkane and has a first bond dissociation energy as high as 439.3 kJ mol −1 [2, 8] .…”
Section: Figurementioning
confidence: 99%
“…Efficient utilization of CH 4 is an imperative task. [1][2][3][4][5][6][7] CH 4 is the most thermodynamically stable alkane and has a first bond dissociation energy as high as 439.3 kJ mol À1 . [2,8] The chemical inertness of CH 4 make its conversion energy-intensive, reflected by industrial production of hydrogen (H 2 ) based on the highly endothermic methane steam reforming (MSR, CH 4 + 2 H 2 OÐCO 2 + 4 H 2 ) at temperatures higher than 700 8C.…”
mentioning
confidence: 99%
“…Thus, Li et al. combined AC−HAADF−STEM with in situ TEM to observe the formation of Ni SACs from Ni NPs [145] . As shown in Figures 8a‐8c, the transformation from Ni NPs to Ni SACs can be gradually completed in the first 3 h, accompanied with the explosion of surface holes.…”
Section: Characterization Of Sacsmentioning
confidence: 99%
“…(a)-(d) ACÀ HAADFÀ STEM images of Ni SACs, and (e) in situ TEM images of the evolution from Ni NPs to Ni SACs. [145] Reprinted with permission from ref [145], Copyright 2019 John Wiley and Sons.…”
Section: Electron Microscopy With Atomic Resolutionmentioning
confidence: 99%